2019
DOI: 10.3389/fphar.2019.00153
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Nrf2 in Experimental Ischemic Stroke

Abstract: Ischemic stroke is one of the leading causes of death and long-term disability worldwide; however, effective clinical approaches are still limited. The transcriptional factor Nrf2 is a master regulator in cellular and organismal defense against endogenous and exogenous stressors by coordinating basal and stress-inducible activation of multiple cytoprotective genes. The Nrf2 network not only tightly controls redox homeostasis but also regulates multiple intermediary metabolic processes. Therefore, targeting Nrf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
110
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 215 publications
1
110
0
2
Order By: Relevance
“…24,28 Indeed, Nrf2/ARE signalling activation protects neurons against OGD/R-induced injury in vitro and cerebral ischaemia/reperfusion-induced injury in vivo. 46,47 In this study, we identified Nrf2/ARE signalling as the downstream target of the miR-148b-3p/Sestrin2 axis.…”
Section: Discussionmentioning
confidence: 87%
“…24,28 Indeed, Nrf2/ARE signalling activation protects neurons against OGD/R-induced injury in vitro and cerebral ischaemia/reperfusion-induced injury in vivo. 46,47 In this study, we identified Nrf2/ARE signalling as the downstream target of the miR-148b-3p/Sestrin2 axis.…”
Section: Discussionmentioning
confidence: 87%
“…Nrf2 plays an indispensable role in maintaining cellular homeostasis. Substantial lines of evidence have suggested that it is bene cial for CNS diseases, including TBI [13][14][15]. Under physiologic conditions, Nrf2 binds with Keap1 in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of studies supported the upregulation of Nrf2 after cerebral ischemia, while some studies indicated suppression of Nrf2. These discrepancies might be due to different experimental factors such as animal strain, age, animal model, et al (Liu et al., 2019) Multiple evidence supporting the neuroprotective effect of Nrf2 against ischemia was obtained from Nrf2 knockout (Nrf2 −/− ) mice. Nrf2 knockout mice showed exacerbated brain damage and neurological deficits after ischemic stroke compared with the wild‐type controls (Liu et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies might be due to different experimental factors such as animal strain, age, animal model, et al (Liu et al., 2019) Multiple evidence supporting the neuroprotective effect of Nrf2 against ischemia was obtained from Nrf2 knockout (Nrf2 −/− ) mice. Nrf2 knockout mice showed exacerbated brain damage and neurological deficits after ischemic stroke compared with the wild‐type controls (Liu et al., 2019). Previous study showed that Nrf2 −/− mice are more sensitive to hyperoxic lung injury compared with wild‐type mice (Cho et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation